Instituciones y costos de negociación-supervisión entre productores de café en el Estado de México: 2020; Institutions and bargaining-monitoring costs among coffee growers in the State of Mexico: 2020 - Celso Rodrigo Rivera Rojo; Wendy Ovando Aldana; Pablo Mejía Reyes (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– The aim of this research is to analyze the relationship between formal and informal institutions with transaction costs (bargaining and monitoring) of coffee growers in the State of Mexico. For this purpose, a measurement instrument was constructed based on a literature review and the participation of key actors, whose construct validity was evaluated through an exploratory factor analysis. The questionnaire was applied to 100 coffee growers during the year 2020. Subsequently, the factor loads for everyone were extracted and stratified to estimate a binary logistic regression model. Findings suggest that informal institutions such as trust, cooperation links and reciprocity were statistically significant with negative coefficients, which implies that an informal institutional frame reduces transaction costs. In contrast, belonging to a producer organization and receiving technical advice from the Apoyos a Peque\~nos Productores program in its Extensionismo component were not statistically significant.
Keywords: D02; D23; Q12; Q13; 330; Ransaction costs; Bargaining costs; Monitoring costs; Institutions; Agricultural markets; Exploratory Factorial Analysis; Logistic regression